Interior design using augmented reality - Tan Poh, Yee (2013)
This project provides the public with an attractive and interactive interior design application using Augmented Reality. Nowadays, there are a lot of people familiar with the computer system and communication technologies. Hence this exploring the prospect of a new form of Virtual Reality (VR) application called Augmented Reality (AR) technology develops more rapidly. Augmented reality is a field of research which deals with the combination of real-world and virtual environment. It is an environment that applies between virtual reality and real environment. There are several problems induce me to create an interior design application in AR. Nowadays, people are busy with their work. People are no time to go to various stores to buy furniture for their home, shop or office. There is difficult to fulfil the customers contentment of decorate their room without imaginary picture to refer. Printed furniture catalog is basically a paper based information with lots of texts and images which does not provide any interaction for the user. And people can‟t view a better graphics of visualization because the design layout is statically presented on papers. Due to that, AR and 3D technology must be applied into interior design area. It is an application which includes furniture and furnishings will develop in three-dimensional surface of object and present by using augmented reality. It will perform the interactive and attract the attention from the public. In this project, I choose Waterfall methodology as a guideline to develop my product throughout this project. By having a methodology, I can carry out my project successfully. As we know, augmented reality technology is still new in our country, but it is a fact that AR technologies would potentially to be the future technology trend to the public.